2020
DOI: 10.3390/coatings10080755
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Structural, Mechanical and Frictional Properties of MoSx Coatings by High-Power Impulse Magnetron Sputtering

Abstract: Tribology, as the science and technology of interacting surfaces, typically relies on liquid lubricants which reduce friction and wear. For environmentally friendly tribological purposes and applications requiring a liquid-free performance, solid lubricants, such as MoS2 coatings, play an essential role. It is crucial to understand the interplay between the parameters of the coating synthesis and the characteristics of the coating. The impact of the deposition parameters on the structural, mechanical and frict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…That is, the following growth pattern exists where the MoS 2 coating grows first into a dense coherent layer with (002) basal orientation and then into a loose columnar structure with (h k 0) edge orientation (Gao et al , 2017). Diffraction peaks are clearly observed for pure MoS 2 coatings at 2θ of about 11°, 33° and 59°, referring to (002), (100) and (110) crystal plane, respectively (Kokalj et al , 2020). However, the intensity value of the (002) peak increases and the peak becomes wider as the sputtering current of the V target increases.…”
Section: Resultsmentioning
confidence: 99%
“…That is, the following growth pattern exists where the MoS 2 coating grows first into a dense coherent layer with (002) basal orientation and then into a loose columnar structure with (h k 0) edge orientation (Gao et al , 2017). Diffraction peaks are clearly observed for pure MoS 2 coatings at 2θ of about 11°, 33° and 59°, referring to (002), (100) and (110) crystal plane, respectively (Kokalj et al , 2020). However, the intensity value of the (002) peak increases and the peak becomes wider as the sputtering current of the V target increases.…”
Section: Resultsmentioning
confidence: 99%
“…The layers consist of S-Mo-S three-atomic-layer structures held together by weak van der Waals forces between the layers [194,[218][219][220]. In the occurrence of sliding, the crystalline layers of MoS2 will easily slide and orient parallel to the direction of relative movement, which provides the lubricating effect [209,[221][222][223]. On the other hand, the solid ionic bond between S and Mo provides the lamellae a high resistance to asperities penetration.…”
Section: Sulfidesmentioning
confidence: 99%
“…Therefore, improving the process is also essential to improving the performance of MoS 2 -based coatings. Kokalj et al [18] studied the structural changes of MoS x films under pulse frequency and other parameters. They found that low pulse frequency shortened the Mo-S bond length, which could significantly improve the hardness and elastic stiffness of the film.…”
Section: Introductionmentioning
confidence: 99%